Refractive Index Change of Cellulose Nanocrystal-Based Electroactive Polyurethane by an Electric Field - Kim, Jaehwan; Ko, Hyun-U; Kim, Hyun Chan (Frontiers in Bioengineering and Biotechnology, 2021)
A tunable optical lens can tune or reconfigure the lens material itself such that it can eliminate the moving part of the lens, which brings broad technological impacts. Many tunable optical lenses have been implemented using electroactive polymers that can change the shape of the lens. However, the refractive index (RI) change of electroactive polymers has not been well investigated. This paper investigated the RI change of CNC-based transparent and electroactive polyurethane (CPPU) in the presence of an actuating electric field. The prepared CPPU was electrically poled to enhance its electro-optical performance, and the poling conditions in terms of frequency and electric field were optimized. The poled CPPU was characterized using a Fourier transform infrared spectroscopy and a refractometer. To investigate the RI change in the presence of an actuating electric field, the poled CPPU was constrained between two electrodes with a fixed distance. The RI linearly increased as the actuating electric field increased. The RI change mechanism and the optimized poling conditions are illustrated. The tunable RI is a promising property for implementing a tunable optical lens.